Collaborative Innovation for Disaster-Resilient Tourism Villages to Enhance Safe Tourism in Indonesia - Muhammad Ridwan Caesar; Nurhadi; Diah Apriliani (Social Science Academic, 2026)
The collaborative model of disaster management is very important in reducing disaster risk in disaster-prone areas, this is no exception for tourist attractions that are often visited by various communities. Bandung Regency has many tourist destinations that are prone to disasters, one of which is the Ciwidey area. Various policies and strategies have been prepared by the government in disaster management in disaster-prone areas including the Ciwidey tourist area. The existence of a Disaster Resilient Village in Bandung Regency is expected to reduce disaster risk. However, the Disaster Resilient Village program has not fully become a solution in disaster management, because villages alone are not enough to handle disasters, collaboration between various parties is needed to create disaster safe areas. The purpose of this study is to determine collaborative strategies for disaster mitigation in disaster-resilient villages in creating disaster-safe tourist areas in Bandung Regency. The stages of the research include identifying the optimization of the implementation of the Disaster Tangguh Village, reviewing government policies related to the Disaster Tangguh Village to then map out collaborative disaster mitigation strategies.